Workforce Planning in Leather Shoe Stitching Line Using Workload Analysis Method at PT X Sidoarjo - Moch Isabil Liwaq; Handy Febri Satoto; Wan Zuki Azman Wan Muhamad (Fakultas Teknik Universitas 17 Agustus 1945 Surabaya, 2026)
The leather shoe manufacturing industry requires efficient production processes to meet output targets and maintain high quality standards. PT X, a leather shoe manufacturer in Sidoarjo, East Java, produces shoes for the International brand. The stitching line at PT X experiences consistent failure to achieve daily production targets, leading to 1–3 hours of overtime per day. This condition indicates that the existing workforce distribution and workload are not yet optimal. This study aims to measure the actual workload of workers on the stitching line and to determine the optimal number of workers using the Workload Analysis (WLA) method. The research was conducted through direct time measurement (stopwatch time study) combined with work sampling to calculate standard time, performance rating, and allowance for each work element. The workload calculation showed that all 18 work elements exceeded 100 percent, with an average workload of 123.17 percent, indicating overload conditions across the line. Based on the WLA method and standard output calculations, the optimal workforce requirement was determined to be 19 workers. A comparative cost analysis demonstrated that employing 19 workers at regular time (IDR 91,200,000/month) is more cost-effective than retaining 18 workers with overtime (IDR 98,565,120/month). These findings provide a quantitative basis for workforce planning decisions in the stitching production line.